Prevalence and Factors Associated With Willingness to Sustain Pandemic-Induced Digital Work in the General Population and Moderating Effects of Screen Hours: Cross-Sectional Study - Jiaying Li; Daniel Yee Tak Fong; Mandy Man Ho; Edmond Pui Hang Choi; Kris Yuet Wan Lok; Jung Jae Lee; WenJie Duan; Janet Yuen Ha Wong; Chia-Chin Lin (JMIR Publications, 2024)
BackgroundThe pandemic has accelerated digital work transformation, yet little is known about individuals' willingness to sustain such digital modes and its associated factors. A better understanding of this willingness and its drivers is crucial for guiding the development of future digital work infrastructure, training programs, and strategies to monitor and prevent related health issues. ObjectiveThis study aims to quantify the general population's willingness to sustain pandemic-induced digital work, identify its associated factors, and examine how screen time moderates these relationships. MethodsA cross-sectional study was conducted targeting Hong Kong residents aged ≥18 years who have increased engagement in digital work since the pandemic. Data were collected through self-reported, web-based surveys. Descriptive statistics determined prevalence rates, while structured multiphase logistic regression identified associated factors and explored the moderating effects of screen hour levels. ResultsThis unfunded study enrolled 1014 participants from May 2 to June 24, 2022, and completed data analysis within 3 months after data collection. A total of 391 (38.6%; 95% CI 35.6%-41.6%) participants expressed willingness to sustain digital work. Positive factors associated with this willingness included being an employee (odds ratio [OR] 3.12, 95% CI 1.59-6.45; P=.001), being health professionals (OR 3.32, 95% CI 1.49-7.82; P=.004), longer screen hours (OR 1.09, 95% CI 1.03-1.15; P=.002), and higher depression levels (OR 1.20, 95% CI 1.01-1.44; P=.04). Conversely, negatively associated factors included older age (OR 0.87, 95% CI 0.81-0.94; P=.001), extroversion (OR 0.66, 95% CI 0.51-0.86; P=.002), higher eHealth literacy (OR 0.96, 95% CI 0.93-0.98; P<.001), perceived greater susceptibility to COVID-19 (OR 0.84, 95% CI 0.74-0.96; P=.009), residence in a high-severity COVID-19 community (OR 0.73, 95% CI 0.63-0.84; P<.001), having infected individuals in the immediate social circle (OR 0.64, 95% CI 0.46-0.88; P=.006), higher BMI (OR 0.94, 95% CI 0.90-0.99; P=.02), feelings of being out of control (OR 0.96, 95% CI 0.93-0.98; P=.002), and higher fear of COVID-19 (OR 0.96, 95% CI 0.94-0.98; P=.001). In addition, a moderating effect of screen hour level (high: >8 h/d; low: ≤8 h/d) influenced the association among 10 factors related to willingness to sustain pandemic-induced digital work, including age, education level, household size, needs for regular medical care, BMI, frequency of both vigorous and moderate physical activities, perceived COVID-19 severity, immediate social circle COVID-19 presence, and fear of COVID-19 (all P values for interaction <.05). ConclusionsThe substantial willingness of the general population to sustain digital work after the pandemic highlights the need for robust telework infrastructure, thorough monitoring of adverse health outcomes, and the potential to expand telehealth services among this group. The identification of factors influencing this willingness and the moderating role of screen hours inform the development of personalized strategies to enhance digital work acceptance where needed.